2014
DOI: 10.1007/978-3-319-11964-9_38
|View full text |Cite
|
Sign up to set email alerts
|

How Semantic Technologies Can Enhance Data Access at Siemens Energy

Abstract: We present a description and analysis of the data access challenge in the Siemens Energy. We advocate for Ontology Based Data Access (OBDA) as a suitable Semantic Web driven technology to address the challenge. We derive requirements for applying OBDA in Siemens, review existing OBDA systems and discuss their limitations with respect to the Siemens requirements. We then introduce the Optique platform as a suitable OBDA solution for Siemens. Finally, we describe our preliminary installation and evaluation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…The study also shows that the learnability of OptiqueVQS is high as participants did not receive any substantial training. Earlier, three other user experiments were conducted: one with casual users [54] and two others with domain experts at Statoil and Siemens on nonstreaming scenarios [53,25]. These studies revealed similar results and confirmed that OptiqueVQS could address various user types and different scenarios with high efficiency, effectiveness and user satisfaction.…”
Section: T5supporting
confidence: 53%
See 4 more Smart Citations
“…The study also shows that the learnability of OptiqueVQS is high as participants did not receive any substantial training. Earlier, three other user experiments were conducted: one with casual users [54] and two others with domain experts at Statoil and Siemens on nonstreaming scenarios [53,25]. These studies revealed similar results and confirmed that OptiqueVQS could address various user types and different scenarios with high efficiency, effectiveness and user satisfaction.…”
Section: T5supporting
confidence: 53%
“…Therefore, in order to prevent high downtime costs, Siemens runs several service centres, each responsible for remote monitoring and diagnostics of such many thousands of appliances. Data is stored in several thousand databases with varied schemas and the size of the data is in the order of hundreds of terabytes, e.g., there is about 15 GB of data associated to a single turbine, and it currently grows with the average rate of 30 GB per day [25]. Service centres have two main categories of tasks:…”
Section: The Siemens Use Casementioning
confidence: 99%
See 3 more Smart Citations